Chromosome genome assembly for the meagre, Argyrosomus regius, reveals species adaptations and sciaenid sex-related locus evolution - Papadogiannis, Vasileios; Manousaki, Tereza; Nousias, Orestis; Tsakogiannis, Alexandros; Kristoffersen, Jon B.; Mylonas, Constantinos C.; Batargias, Costas; Chatziplis, Dimitrios; Tsigenopoulos, Costas S. (Frontiers in Genetics, 2023)
The meagre, Argyrosomus regius, has recently become a species of increasing economic interest for the Mediterranean aquaculture and there is ongoing work to boost production efficiency through selective breeding. Access to the complete genomic sequence will provide an essential resource for studying quantitative trait-associated loci and exploring the genetic diversity of different wild populations and aquaculture stocks in more detail. Here, we present the first complete genome for A. regius, produced through a combination of long and short read technologies and an efficient in-house developed pipeline for assembly and polishing. Scaffolding using previous linkage map data allowed us to reconstruct a chromosome level assembly with high completeness, complemented with gene annotation and repeat masking. We use this new resource to study the evolution of the meagre genome and other Sciaenids, via a comparative analysis of 25 high-quality teleost genomes. Combining a rigorous investigation of gene duplications with base-wise conservation analysis, we identify candidate loci related to immune, fat metabolism and growth adaptations in the meagre. Following phylogenomic reconstruction, we show highly conserved synteny within Sciaenidae. In contrast, we report rapidly evolving syntenic rearrangements and gene copy changes in the sex-related dmrt1 neighbourhood in meagre and other members of the family. These novel genomic datasets and findings will add important new tools for aquaculture studies and greatly facilitate husbandry and breeding work in the species.